Factor using the identity: a3 + b3 = (a + b)(a2 – ab + b2) z3 + 8 (z + 2)(z2 – 2z + 4)? (z + 2)3?

Question

Factor using the identity: a3 + b3 = (a + b)(a2 – ab + b2)

z3 + 8

(z + 2)(z2 – 2z + 4)?

(z + 2)3?

(z3 + 8)(z2 – 8z3 + 64)?

(z + 8)(z2 – 8z + 64)?

0

Answers ( No )

    0
    2022-01-11T18:07:29+00:00

    Answer:

    the answer is A

    Step-by-step explanation:

    got it right on the assignment

    0
    2022-01-11T18:08:10+00:00

    Given the identity

    a^3 + b^3 = (a + b)(a^2-ab + b^2)

    Then

    z^3 + 8=z^3+2^3 \\  \\ =(z+2)(z^2-2z+2^2) \\  \\ =(z+2)(z^2-2z+4)

Leave an answer

Browse
Browse